APLIKASI ORNAMEN KHAS BUDAYA KECINAAN SEBAGAI CIRI PADA RESTORAN CINA DI JAKARTA - Polniwati Salim (Jurnal Dimensi Seni Rupa dan Desain, 2015)
AbstractA Chinese restaurant is a place where commercial business takes place. It is alsoa place which professionally serves traditional Chinese food for the public.Talking about Chinese restaurants, the topic is obviously connected to ChineseCulture. The importance of Chinese culture holds great importance and is eventhe core point of creating art. The art would be based upon the aesthetic contentswhich contain a symbolic meaning in Chinese philosophy. In a typical chineserestaurant, the connection between tradition and art is represented in the formof ornament that acts functionally, and has specific unique characteristic. Theaesthetical theory about the art of the design and the implementation of chineseornaments also takes part in the study as well.This study was conducted by the qualitative methods with survey, interviewand the documentation of the ornaments in Chinese Restaurant, aiming tointroduce and enrich this knowledge to the worldwild as the ornaments standfor showing the identity of chinese culture. This data would be useful as a sourceof inspiration for the future planning of an interior design. Especially in theapplication of decorating a restaurant that takes the meaning of the decorationalong with the needs, function to be created. AbstrakRestoran Cina merupakan suatu tempat usaha komersial yangmenyediakan jasa pelayanan masakan khas Cina bagi umum dandikelola secara professional. Berbicara tentang restoran Cina, jelas akanterkait dengan persoalan budaya Cina. Nilai budaya mempunyaihubungan erat bahkan mendasari terciptanya suatu keseniankhususnya seni rupa. Seni akan tercermin dan mengarah pada konteksestetika yang mengandung makna simbolis dalam karya seni di manafilosofi Cina menyertai. Dalam restoran Cina, hubungan antara budayadengan seni terwujud dalam bentuk ornament yang bersifat fungsional,benda hias ataupun yang memiliki ciri dan sifat spesifik dan unik khasCina. Teori estetika mengenai bagaimana penggambaran nilaikeindahan dalam penerapan ornament di interior restoran Cina ikutterlibat dalam topik ini.Kajian dilakukan dengan metode kualitatif pendekatan survey danwawancara serta pendokumentasian ornament pada interior restoranCina di Jakarta dengan tujuan untuk memberikan suatu wacana danpenerangan mengenai penerapan ornament yang menjadi petandakultur kecinaan pada restoran tersebut. Sehingga diharapkan data inidapat bermanfaat sebagai sumber inspirasi dalam proses desainperencanaan sebuat interior restoran pada umumnya dan restoran Cina pada khususnya